2015
DOI: 10.1590/2177-6709.20.5.066-071.oar
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorhexidine varnish on gingival growth in orthodontic patients: a randomized prospective split-mouth study

Abstract: Introduction: Fixed orthodontic appliances patients suffer limitations on the effective control of biofilm by mechanical methods, bringing the need of a coadjutant in the control of inflammation and oral health improvement. Objective: The aim of this prospective split-mouth blind study was to analyze the effect of a 40% chlorhexidine (CHX) varnish on gingival growth of patients with orthodontic fixed appliances. Methods: Healthy teenage patients with fixed orthodontic appliances and increased gingival volume w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…A 2015 study in Brazil indicated that chlorhexidine varnish proved effective against gingival overgrowth in patients undergoing orthodontic treatment, recalling that chlorhexidine is considered the gold standard for the chemical control of dental biofilm [34]. In the present research, a reduction in the frequency of gingival enlargement was not found in those patients who referred to the use of chlorhexidine colloquia.…”
Section: Discussioncontrasting
confidence: 44%
“…A 2015 study in Brazil indicated that chlorhexidine varnish proved effective against gingival overgrowth in patients undergoing orthodontic treatment, recalling that chlorhexidine is considered the gold standard for the chemical control of dental biofilm [34]. In the present research, a reduction in the frequency of gingival enlargement was not found in those patients who referred to the use of chlorhexidine colloquia.…”
Section: Discussioncontrasting
confidence: 44%
“…To better compare the influence of modified adhesive to unmodified material, we monitored the change of supragingival microbiome around the brackets bonded with either modified cement (RMD) or unmodified cement (RMGIC) via split-mouth performance to the same cohort. This design has been adopted in multiple studies relevant to oral hygiene or microbial change, which could lessen the individual variation of oral microbiome as much as possible ( Pellegrini et al, 2009 ; Pretti et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the use of 40% chlorhexidine varnish causes a gradual increase in the clinical crown at 14 and 56 days after use. Chlorhexidine varnish has been proved to be effective against gingival overgrowth in patients undergoing orthodontic treatment [ 30 ]. Biocompatibility of dental materials is an important consideration for the patient, clinician, laboratory technician, and manufacturer.…”
Section: Discussionmentioning
confidence: 99%